2020
DOI: 10.1016/j.ijhm.2020.102605
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing hospitality business performance: The role of entrepreneurial orientation and networking ties in a dynamic environment

Abstract: Highlights Implications of the entrepreneurial orientation on short term financial return and long term business growth. Association between dynamic environment and entrepreneurial orientation. Adoption of business and social networking ties in the hospitality industry. Prompting managers' decisions to develop entrepreneurial orientation in creating value for hospitality firms. Gaining short term financial expansion by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
78
0
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(131 citation statements)
references
References 145 publications
(163 reference statements)
5
78
0
9
Order By: Relevance
“…Within the entrepreneurial orientation, several dimensions were considered, as Doherty et al [73] indicated that the evaluation of performance in organisations, perceived quality and sporting performance level in this case, must be analysed from a multidimensional perspective. This entrepreneurial orientation has been widely studied in organisational environments [12,74].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Within the entrepreneurial orientation, several dimensions were considered, as Doherty et al [73] indicated that the evaluation of performance in organisations, perceived quality and sporting performance level in this case, must be analysed from a multidimensional perspective. This entrepreneurial orientation has been widely studied in organisational environments [12,74].…”
Section: Discussionmentioning
confidence: 99%
“…Entrepreneurial orientation (hereinafter: EO) can be understood as a feature of the model of direction and management of the organisation, e.g., towards change through initiatives and activities that encourage innovation, proactivity, and risk taking [12]. Complementarily, a recent article published by Wales et al [13] goes further and states that "EO can be recognized as a concept which includes entrepreneurial top management style, organisational configuration, and new entry initiatives".…”
Section: Entrepreneurial Orientationmentioning
confidence: 99%
“…Orientasi wirausaha sering disebut sebagai pembuatan strategi kewirausahaan yang dicirikan sebagai atribut gaya manajemen yang mendukung perubahan dan mendukung kegiatan yang berkaitan dengan pemanfaatan berbagai bentuk inovasi, pengembangan produk / layanan baru dan penciptaan nilai pelanggan yang unggul ( (Tajeddini & Trueman, 2016). Orientasi wirausaha adalah konstruksi gabungan dari proses, struktur, dan perilaku perusahaan yang dicirikan oleh inovasi, proaktif, dan pengambilan risiko (Sahaym et al, 2021 pengembangan produk dan layanan baru serta mengantisipasi dan menanggapi kemungkinan perubahan (Tajeddini et al, 2020). Orientasi wirausaha didukung oleh orientasi strategis yang berbeda yang secara kolektif meningkatkan hasil bisnis dengan menciptakan pengetahuan baru yang diperlukan untuk membangun kemampuan baru dan memperkuat kembali sumber daya dan kemampuan yang ada, mendorong pola pikir inovatif dalam perusahaan di bawah lingkungan yang bergolak dan kompetitif yang berbeda (Cavusgil & Knight, 2015); (Jalilvand et al, 2018); (Martin & Javalgi, 2016); (Taheri et al, 2019).…”
Section: Orientasi Wirausahaunclassified
“…Open Innovation yang dimaksud adalah sebuah proses pemanfaatan ide-ide inovatif yang berasal dari eksternal perusahaan sehingga dapat mempercepat inovasi dan memperluas pasar suatu perusahaan (Lyu, Zhu, Han, He, & Bao, 2020). Open Innovation berpihak pada perubahan dan mendukung kegiatan yang berkaitan dengan pemanfaatan berbagai inovasi seperti pengembangan produk / jasa baru, dan penciptaan nilai pelanggan yang unggul (Tajeddini, Martin, & Ali, 2020). Sedangkan, Pengelolaan Risiko yang dimaksud adalah proses dan mekanisme dimana keputusan berisiko diambil dan diimplementasikan dalam suatu perusahaan (Krauß & Bremer, 2020).…”
unclassified